Outcome of Childhood Acute Lymphoblastic Leukaemia after Induction Therapy --- Three-Year Experience in a Tertiary Care Hospital in Bangladesh (Journal of Enam Medical College, 2017)
Background: The incidence of different malignancies is increasing among the world populations. Acute lymphoblastic leukaemia (ALL) is the most common of all the paediatric malignancies. Response to induction therapy is one of the most important predictors of long term outcome of ALL.Objective: To see the immediate outcome of paediatric ALL patients following induction therapy.Materials and Methods: This retrospective study was conducted from January 2013 to December 2015. Total 221 paediatric ALL patients were included in this study. Diagnosis was based on history, examination, blast cells count on peripheral blood film and bone marrow study, CSF study and immunophenotyping of peripheral blood/bone marrow aspirate in patients who were financially capable. Among them, parents of 40 (18%) patients did not agree to start chemotherapy. According to Modified UK ALL 2003 protocol (Regimen A & B) 181 patients were given induction therapy (vincristine, prednisolone, L-asparaginase, and daunomycin) in high risk patients. Among them 14 patients discontinued, 10 patients died during chemotherapy and rest 157 patients completed induction phase. Bone marrow study was repeated after completion of induction therapy and remission pattern was seen.Results: Out of 157 chemotherapy completed patients, 137 (87%) went into complete remission (25% blast cells in the bone marrow). Ten (5.5%) patients died due to bleeding, febrile neutropenia and sepsis during the course of induction therapy.Conclusion: ALL in children is curable with effective chemotherapy. Poverty, ignorance and misconception regarding outcome are responsible for refusal and discontinuation of chemotherapy in third world countries like Bangladesh. Mortality and treatment cost can be reduced with the improvement of the facilities for isolation, barrier nursing and supportive treatment, and by creating awareness.J Enam Med Col 2017; 7(1): 25-28